Linking E-WOM to Muslimah Consumer Buying Intention through the Shopee Application: The Role of Brand Image as a Mediating Variable - Zakiy, Muhammad; Eggy, Sherlinda; As’ad, Syarif (Journal of Islamic Economics and Social Science (JIESS), 2022)
This study aims to examine the effect of Electronic Word of Mouth (E-WoM) on consumer buying interest in the Shopee application through brand image as a mediating variable. This study used a quantitative descriptive method with a purposive sampling technique to obtain a sample of 200 respondents who had purchased Rabbani products through the Shopee application. The data collection technique was carried out by distributing online questionnaires via Google form using a Likert scale of points 1 to 5, which were analyzed using SPSS Version 26 through the classical assumption test, path analysis, and Sobel test. The results show that E-WoM has a positive effect on brand image, brand image has a positive effect on buying interest, E-WoM has a positive effect on consumer buying interest in Rabbani products, E-WoM has a positive effect on buying interest through brand image as mediation partial, meaning that the greater the E-WoM, the brand image will increase so that the buying interest will be higher.